An aging population : opposing viewpoints - Cozic, Charles P., 1957- (San Diego, CA : Greenhaven Press, 1996)
Presents twenty-six articles debating issues related to aging in America, discussing the economics of supporting seniors' entitlement programs, retirement and illness, health care, and the social perception of the elderly.
Includes bibliographical references (p. 208-209) and index.
School Library Journal.
Wilson's Junior High School.
Wilson's Senior High School.
Young Adult.
Young Adult
Keywords: Old age assistance -- United States; Older people -- Government policy -- United States; Older people -- Medical care -- United States; Older people -- United States -- Public opinion; Older people -- United States -- Social conditions; Public opinion -- United States; Elderly -- United States -- Government policy; Elderly -- United States -- Medical care; Elderly -- United States -- Public opinion; Elderly -- United States -- Social conditions; Public opinion